2020
DOI: 10.1111/1365-2435.13606
|View full text |Cite
|
Sign up to set email alerts
|

Climate and soil micro‐organisms drive soil phosphorus fractions in coastal dune systems

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 81 publications
(94 reference statements)
0
18
1
Order By: Relevance
“…2 ), which can be explained by the accumulation of soil total P in the topsoil 28 , 29 . The large-scale precipitation and temperature on the uppermost soil layer can enhance bedrock and soil chemical weathering rates 23 and stimulate soil total P accumulation in the topsoil profile 30 . Our results also demonstrated, via random forest models and linear regression analyses, that the effect size and importance of climate factors for topsoil layers were higher than those for subsoil layers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ), which can be explained by the accumulation of soil total P in the topsoil 28 , 29 . The large-scale precipitation and temperature on the uppermost soil layer can enhance bedrock and soil chemical weathering rates 23 and stimulate soil total P accumulation in the topsoil profile 30 . Our results also demonstrated, via random forest models and linear regression analyses, that the effect size and importance of climate factors for topsoil layers were higher than those for subsoil layers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the vertical distribution patterns of soil total P may also be explained by the effect of biotic and abiotic factors and the multiple pathways resulting in soil layer differences 30 . Soil properties 30 , plant litter inputs 32 , root system secretion 33 , enzyme activities 34 , and microbial decomposition 35 are known to decrease with increasing soil depth; these factors are ultimately dependent on large-scale climate patterns, because climate affects the distribution of soil total P by controlling the rates of both geochemical weathering and biological activities 30 , 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides spatial patterns of soil P fractions, their dominant drivers have also attracted considerable attention (Garcia‐Velazquez et al., 2020; Hou, Chen, et al., 2018; Luo et al., 2021; Martin‐Sanz et al., 2021). However, previous studies were mainly confined to climatic and edaphic properties (Hou, Chen, et al., 2018), and little information is available about how soil microbial properties (e.g., microbial biomass, community composition and phosphatase activity) and minerals (e.g., Fe/Al‐(hydr) oxides and carbonate minerals) regulate various soil P fractions over broad geographic scale (Martin‐Sanz et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, changes in the fractions of soil P in bamboo‐chicken farms can largely determine the soil P availability, which in turn affects microbial community structure and bamboo forest production. The dynamics of P fraction content depends on various factors, such as soil texture, climatic environment, microorganisms, and land use (Maharjan, Maranguit, & Kuzyakov, 2018; Velázquez et al, 2020). Previous studies have shown that overgrazing may hinder the mineralization of phosphorus (Ford, Roberts, & Jones, 2016) and reduce its solubility (Sigua, Chase, & Albano, 2014).…”
Section: Introductionmentioning
confidence: 99%